FORMULATION AND EVALUATION OF GASTRORETENTIVE MICROBALLOONS OF ACEBROPHYLLINE FOR THE TREATMENT OF BRONCHIAL ASTHMA - S, Bhuvaneswari; MANIVANNAN S; M, Akshay; F, Nify (Asian Journal of Pharmaceutical and Clinical Research, 2016)
Objective: Gastroretentive dosage forms are an approach for prolonged and predictable drug delivery in the upper gastrointestinal tract to control the gastric residence time. Microballoons are considered as one of the most promising buoyant drug delivery systems as they possess the advantages of both multiple-unit systems and good floating properties. Acebrophylline is a xanthine derivative with potent bronchodilator, mucosecretolytic, and anti-inflammatory property. It is used to treat bronchial asthma and chronic obstructive pulmonary diseases. Methods: Microballoons of acebrophylline were prepared by emulsion solvent diffusion method using hydroxypropyl methylcellulose (HPMC) and ethyl cellulose (EC) as polymer. The microballoons were evaluated with their micromeritic properties, particle size, tapped density, compressibility index, angle of repose, percentage yield, in vitro buoyancy, entrapment efficiency, drug-polymer compatibility, scanning electron microscopy (SEM), and drug release kinetics. Results: The mean particle size of the microballoons formulation MB1 to MB6 containing HPMC and EC was in the range between 226Â±16 and 577Â±10, respectively. The mean particle size of microballoons was found to increase with increasing polymer concentration. The micromeritic properties were found be good, and SEM confirmed their hollow structure with smooth and dense which helped to prolong floating to increase residence time in stomach. The in vitro drug release studies showed controlled release of acebrophylline microballoons in the simulated gastric fluid more than 12 hrs. Conclusions: The results showed that the prepared floating microballoons of acebrophylline prove to be potential multiple-unit delivery devices adaptable for safe and effective sustained drug delivery. Keywords: Microballoons, Acebrophylline, Bronchial asthma, Hydroxypropyl methylcellulose, Ethyl cellulose.